HPS protects the liver against steatosis, cell death, inflammation, and fibrosis in mice with steatohepatitis. (22nd March 2022) - Yang, Yang; Liu, Xian; Chen, Hui; Wang, Pengjun; Yao, Songhui; Zhou, Bin; Yin, Ronghua; Li, Changyan; Wu, Chutse; Yang, Xiaoming; Yu, Miao
Abstract : Hepassocin (HPS) is a hepatokine associated with metabolic regulation and development of non‐alcoholic steatohepatitis (NASH). However, previous reports on HPS are controversial and its true function is not yet understood. Here, we demonstrated that hepatic HPS expression levels were upregulated in short‐term feeding and downregulated in long‐term feeding in high‐fat diet (HFD)‐ and methionine‐ and choline‐deficient (MCD) diet‐fed mice, as well as in genetically obese ( ob/ob ) mice. HFD‐ and MCD‐induced hepatic steatosis, inflammation, apoptosis, and fibrosis were more pronounced in HPS knockout mice than in the wild‐type mice. Moreover, HPS depletion aggravated HFD‐induced insulin resistance. By contrast, HPS administration improved MCD‐ or HFD‐induced liver phenotypes and insulin resistance in HPS knockout and wild‐type mice. Mechanistic studies revealed that MCD‐induced hepatic oxidative stress was significantly increased by HPS deficiency and could be attenuated by HPS administration. Furthermore, palmitic acid‐induced lipid accumulation and oxidative stress were exclusively enhanced in HPS knockout hepatocytes and diminished by HPS cotreatment. These data suggest that HPS ameliorates NASH in mice, at least in part, by inhibiting the oxidative stress. HPS expression levels are downregulated in human fatty liver tissues, suggesting that it may play an important protective role in NASH. Collectively, our findings provide clear genetic evidence that HPS has beneficial effects on the development of steatohepatitis in mice and suggest that upregulating HPS signaling may represent an effective treatment strategy for NASH. Abstract : Hepassocin (HPS) is a hepatokine that is associated with metabolic regulation and the development of non‐alcoholic steatohepatitis. In HPS knockout mice, diet‐induced hepatic steatosis, inflammation, apoptosis and fibrosis were more pronounced than in wild‐type mice. Moreover, transient HPS was upregulated during disease progression. By contrast, HPS administration improved diet‐induced liver phenotypes. Hepatic oxidative stress was enhanced significantly by HPS deficiency, and HPS attenuates lipotoxicity in hepatocytes.